2008
DOI: 10.2527/jas.2007-0780
|View full text |Cite
|
Sign up to set email alerts
|

Carcass composition and meat quality of equally mature kids and lambs1

Abstract: Carcass composition and meat quality attributes of 55 suckling kids (27 males and 28 females) and 57 suckling lambs (28 males and 29 females) of Portuguese native breeds were investigated. These suckling kid and lamb meats are European meat quality labels produced according to "Cabrito de Barroso-PGI" and "Borrego Terrincho-PDO" specifications, respectively. Female kids were slaughtered at 9.1 ± 0.36 kg of BW, and male kids were slaughtered at 10.4 ± 0.37 kg of BW, corresponding to 20.1 and 17.7% of maturity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
38
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 27 publications
18
38
3
5
Order By: Relevance
“…Although feeding system in this study appeared to have no effect on thawing loss, cooking loss, pH 24 , a number of studies have reported that these parameters do change along with changes in feeding system (Skapetas et al, 2006;Rodriguez et al, 2008;Santos et al, 2008). However, our findings are in agreement with the findings of Cerdeno et al, (2006) who found no significant differences neither in meat pH value nor in colour between different feeding practices.…”
Section: Resultssupporting
confidence: 37%
See 2 more Smart Citations
“…Although feeding system in this study appeared to have no effect on thawing loss, cooking loss, pH 24 , a number of studies have reported that these parameters do change along with changes in feeding system (Skapetas et al, 2006;Rodriguez et al, 2008;Santos et al, 2008). However, our findings are in agreement with the findings of Cerdeno et al, (2006) who found no significant differences neither in meat pH value nor in colour between different feeding practices.…”
Section: Resultssupporting
confidence: 37%
“…However, many studies have demonstrated differences in carcass and meat quality between older lambs under intensive feeding and pasture-based systems (Carrasco et al, 2009, Luciano et al, 2009, Barbut, 2014. Animals fattened under these two different systems had significantly different carcass fat and meat colour (Barwick, 1980, Priolo et al, 2002, Rodriguez et al, 2008, fatness status (Santos et al, 2002;Santos et al,2008) and meat flavor (Saňudo et al, 2000). Our results related to meat colour disagree with the results of (Peña et al (2005) As shown in Table 5, texture parameters were lower in intensively fed lamb compared to the traditional fed lambs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two halves of carcass were weighed and each was divided into five commercial cuts according to Santos et al (2008). These cuts were leg, shoulder, loin, rib/flank and neck which were weighed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it is important to encourage market diversification, enabling product differentiation and value adding. One such strategy may include the production of suckling lambs, a product that plays an important role in various countries in the European Union (Velasco et al, 2000;Osorio et al, 2008;Santos et al, 2008). lt is expected that such changes will increase producer income and profitability, substantially enhancing sector development and thus creating a sustainable lamb production system over time.…”
Section: Introductionmentioning
confidence: 99%